기능성 소화불량증 환자의 위배출시간에 따른 위전도 ( EGG ) 에 관한 연구 - 박영숙; Y . S . Park; 김영수; Y . S . Kim; 강한걸; H . G . Kang; 함기백; K . B . Hahm; 김진홍; J . H . Kim; 조성원; S . W . Cho; et al. (The Korean journal of medicine, 1996)
Objectives " The aim of this study was to know the clinical significance of electrogastrography(EGG) and to determine the relationship between gastric myoelectrical activity and gastric emptying time in patients with functional dyspepsia. Methods: This study included 10normal subjects and 30patients with functional dyspepsia. They were given scrambled egg with 2mCi 99m Tc-sulfur colloid for measuring gastric emptying time. We measured half time(T1/2) and remnant radio activity at 2hour after meal. Gastric myoelectrical activity was recorded by cutaneous EGG(Synetics, Digitrapper EGG) in 30patients with functional dyspepsia. EGG was recorded for at least 30minutes in fasting state and 30minutes in post prandial state (solid test meal, 618Cal), EGG was analyzed based on the running power spectra. Results: 1) In 10 normal subjects, the mean of gastric emptying time (Tl/2) was 89.0±7.9min and among 30 patients of functional dyspepsia, 14patients (46%) showed delayed GET (delayed GET group) and 16patients (53%) showed normal GET (normal GET grooup) 2) In both patients group, there was no significant difference in the percentage of normal gastric slow waves(2-4cpm) between fasting state and post prandial state. 3) In post prandial state, the ratio of slow wave in normal GET group was significantly higher than that in delayed GET group (95.5±6.2% vs 82.5±14.3%, p<0.05), but in fasting state, there was no significant difference. 4) Normal post prandial amplitude increment (1.5times higher than fasting state amplitude) was seen in 7(50%)cases of delayed GET group and in 13(80%)cases of normal GET gorup, which was statistically significant (p<0.05). Conclusion: Among patients with functional dyspepsia, delayed GET group showed higher ratio of gastric dysrhythmia and abnormal post prandial amplitude change. Electrogastrography seems to have clinical significance in evaluating the explanable cause of functional dyspepsia.